Kidney Procurement System in Colombia: A System Dynamics Approach (2019)
Objective: This paper presents an analysis of two regulatory proposals in response to the growing demand for kidney transplants in Colombia. The results can be useful in evaluating these possible policy interventions once they have been implemented. Methods: The proposed model uses System Dynamics as a tool to understand the behavior of this complex social system if two intervention projects are executed. The first is a bill of law seeking to expand the legal presumption of organ donation. The second one is to implement a Kidney Exchange Program. The analysis is made in two parts. Firstly, a causal loop diagram is proposed. Secondly, the simulation of the system using a stock and flow diagram is analyzed. Results: Results show that the projects can balance the system and encourage donations. Conclusion: The implementation of a KEP is recommended since it achieves stability of the system earlier than the amendment to the law, with a reduction in the waiting list size.